2016
DOI: 10.1007/s00701-016-2806-4
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the retrocorporeal artery: a rare cause of spontaneous spinal epidural haematoma

Abstract: A 22-year-old man presented with a sudden backache and paraplegia (ASIA = B). Magnetic resonance imaging showed an anterior pan-spinal epidural haematoma. Digital subtraction angiography was performed and ruled out an underlying vascular malformation but showed an active contrast media leakage into the T-4 ventral epidural space with a pattern of pseudo-aneurysm. A rupture of a T-4 retrocorporeal artery was considered as the aetiology, possibly caused by a haemorrhagic sub-adventitial dissection. Treatment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Priola et al 16 described a review of the literature in which they found a total of 11 cases in which patients experienced low back pain associated with SAH or SSEH due to dissection aneurysm of a radiculomedullary artery mainly at the thoracic level. In the same sense, Guédon et al 1 describe the case of a 22-year-old patient with no significant previous history who presented sudden back pain and paraplegia and underwent a spinal MRI showing SSEH that extended from C1 to L5; after a consensus the authors decided to perform full cerebral and spinal digital subtraction angiography where they found a dissecting aneurysm of T4 for which they opted for an endovascular occlusion and surgical decompression of the level with an adequate postoperative evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Priola et al 16 described a review of the literature in which they found a total of 11 cases in which patients experienced low back pain associated with SAH or SSEH due to dissection aneurysm of a radiculomedullary artery mainly at the thoracic level. In the same sense, Guédon et al 1 describe the case of a 22-year-old patient with no significant previous history who presented sudden back pain and paraplegia and underwent a spinal MRI showing SSEH that extended from C1 to L5; after a consensus the authors decided to perform full cerebral and spinal digital subtraction angiography where they found a dissecting aneurysm of T4 for which they opted for an endovascular occlusion and surgical decompression of the level with an adequate postoperative evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous spinal epidural hematoma (SSEH) associated with spinal subarachnoid hemorrhage (SAH) caused by dissection of a radiculomedullary artery is a pathological entity not described in the literature and therefore its prevalence is unknown. 1 , 2 SSEH due to dissection of a radiculomedullary artery is usually associated with minor spinal trauma or spinal puncture as in the case of spinal anesthesia. 3 On the other hand, spontaneous SSEH are even more rare and have been described mainly in patients with some type of coagulopathy, anticoagulant therapy, intraspinal tumors, or arteriovenous fistulas, and cases with no underlying structural cause are a diagnostic challenge as a cause of low back pain.…”
mentioning
confidence: 99%
“…It can be summarized as the accumulation of blood in the vertebral epidural space without trauma or iatrogenic procedure performed (e.g., lumbar puncture) [6]. Coagulopathy [7,8], vascular malformations [9,10] and hemorrhagic tumors are considered to cause SSEH by some authors [11]. The others represent the stand that only those SSEH that are purely idiopathic can be labeled as spontaneous [12,13].…”
Section: Discussionmentioning
confidence: 99%